Comparison of nasopharyngeal and oropharyngeal swabs for SARS-CoV-2 detection in 353 patients received tests with both specimens simultaneously. (May 2020) - Wang, Xiong; Tan, Li; Wang, Xu; Liu, Weiyong; Lu, Yanjun; Cheng, Liming; Sun, Ziyong
Highlights: Nasopharyngeal swab showed higher positive rate than oropharyngeal swab. Nasopharyngeal swab from male showed higher positive rate than female. The consistency between from nasopharyngeal and oropharyngeal swabs were poor. Abstract: Background: Since the outbreak of coronavirus disease (COVID-19) in Wuhan in December 2019, by March 10, 2020, a total of 80, 932 confirmed cases have been reported in China. Two consecutively negative RT-PCR test results in respiratory tract specimens is required for the evaluation of discharge from hospital, and oropharyngeal swabs were the most common sample. However, false negative results occurred in the late stage of hospitalization, and avoiding false negative result is critical essential. Methods: We reviewed the medical record of 353 patients who received tests with both specimens simultaneously, and compared the performance between nasopharyngeal and oropharyngeal swabs. Results: Of the 353 patients (outpatients, 192; inpatients, 161) studied, the median age was 54 years, and 177 (50.1%) were women. Higher positive rate (positive tests/total tests) was observed in nasopharyngeal swabs than oropharyngeal swabs, especially in inpatients. Nasopharyngeal swabs from inpatients showed higher positive rate than outpatients. Nasopharyngeal swabs from male showed higher positive rate than female, especially in outpatients. Detection with both specimens slightly increased the positive rate than nasopharyngeal swab only. Moreover, the consistency between from nasopharyngeal and oropharyngeal swabs were poor (Kappa = 0.308). Conclusion: In conclusion, our study suggests that nasopharyngeal swabs may be more suitable than oropharyngeal swab at this stage of COVID-19 outbreak.